How high should boys sing? [ gender, authenticity and credibility in the young male voice - Ashley, Martin , 1953- (Ashgat, 2009)
Martin Ashley presents a unique consideration of boys' singing that shows the high voice to be historically, culturally and physiologically more problematic even than is commonly assumed. Through Ashley's extensive conversations with young performers and analysis of their reception by 'peer audiences', the research reveals that the common supposition that 'boys don't want to sound like girls' is far from adequate in explaining the 'missing males' syndrome that can perplex choir directors. The book intertwines the study of singing with the study of identity. --from publisher description